Agronomic and physiological evaluation in sweet potato (Ipomoea batatas) clones subjected to hydric stress conditions - León-Pacheco, Rommel Igor (2021)
Introduction. Roots and tubers, such as sweet potatoes (Ipomoea batatas L.), are among the top six most important crops worldwide. However, this species is sensitive to stress due to water deficit. The use of drought resistant genotypes and better water management practices can enhance its’ root quality and yield. In order to enhance productivity in those environments, complementary irrigation practices can be used or genotypes with promising yield potential against these conditions can be identified. Objective. To evaluate the effect of water stress on physiological and agronomic variables in sweet potato clones. Materials and methods. A trial was conducted from April to July 2015 at the National Center for Agricultural Research, Maracay, Venezuela, with three replications under a split plot design, where the principal plot was integrated by three irrigation treatments (all cycles, two, and three first months with irrigation) and the secondary plot by three sweet potatoes clones. Variables associated with gas exchange, vegetative growth, biomass, and yield were measured. Results. The results show that sweet potato plants against drought conditions decreased their growth, foliar expansion, partially closed the stomata avoiding water losses through transpiration without affecting the variables of net assimilation rate of CO2, yield, and biomass accumulation. The best clone with increased transpiration, biomass accumulation, and yield of 18.3 t ha-1 was the 64. Irrigation throughout the crop cycle generated the highest vegetative growth with 125 leaves plant-1. Conclusions. Under water stress conditions, sweet potato plants adapted physiologically to avoid water loss through transpiration without sacrificing photosynthetic rates, with which the clones were able to accumulate aerial biomass, roots, and tuber yield similar to the irrigated crop.